2001
DOI: 10.1002/jmri.1164
|View full text |Cite
|
Sign up to set email alerts
|

Extent and time course of morphological changes of bone marrow induced by granulocyte‐colony stimulating factor as assessed by magnetic resonance imaging of healthy blood stem cell donors

Abstract: The aim of this study was to assess the time course and extent of signal alterations of red bone marrow after shortterm stimulation by recombinant human granulocyte-colony stimulating factor (rHuG-CSF) in healthy peripheral blood stem cell donors using magnetic resonance imaging (MRI) at low-field strength. Twelve healthy blood stem cell donors without evidence of bone marrow disorders were prospectively investigated and underwent four MRI studies of their lumbar spine. Sagittal T1-and T2-weighted spin-echo se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
14
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 23 publications
(62 reference statements)
3
14
1
Order By: Relevance
“…Similar observations have been reported in healthy blood stem cell donors after application of hematopoietic growth factors (4,8). The underlying process of a relative increase of the water fraction in relation to the fatty component is similar for hematological diseases and stimulated hematopoiesis (1,4). Opposedphase gradient-echo (GE) sequences are sensitive to changes of the fat-to-water ratio (9) and are therefore especially suitable for imaging bone marrow (10).…”
supporting
confidence: 66%
See 3 more Smart Citations
“…Similar observations have been reported in healthy blood stem cell donors after application of hematopoietic growth factors (4,8). The underlying process of a relative increase of the water fraction in relation to the fatty component is similar for hematological diseases and stimulated hematopoiesis (1,4). Opposedphase gradient-echo (GE) sequences are sensitive to changes of the fat-to-water ratio (9) and are therefore especially suitable for imaging bone marrow (10).…”
supporting
confidence: 66%
“…Due to the rise in marrow cellularity, the signal intensity (SI) increases in turbo inversion-recovery sequence with short inversion time (TIRM) images and decreases in T1-weighted (T1-w) spin-echo (SE) sequences (7). Similar observations have been reported in healthy blood stem cell donors after application of hematopoietic growth factors (4,8). The underlying process of a relative increase of the water fraction in relation to the fatty component is similar for hematological diseases and stimulated hematopoiesis (1,4).…”
supporting
confidence: 60%
See 2 more Smart Citations
“…Very few prospective studies investigated post-chemo MR signal changes. Altehoefer et al found a signifi cant 33 % increase in signal intensity on STIR images at the fi rst scan, 26 days following induction chemotherapy, refl ecting temporary bone marrow edema, normalizing shortly after peripheral stem cell transplantation and G-CSF (Altehoefer et al 1997(Altehoefer et al , 2001 ). Within 1-2 weeks, chemotherapy causes a myeloid depletion with a decrease in marrow cellularity and fatty marrow replacement with an increase in signal intensity on T1-weighted images and a low signal intensity on fat-suppressed sequences.…”
Section: Chemotherapy-induced Changes In Normal Bone Marrowmentioning
confidence: 99%